Perlindungan Hukum Terhadap PT Pegadaian Atas Barang Jaminan Hasil Tindak Pidana - Priskila Ch.N Watania (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study aims to determine the form of protection of Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector (P2SK) against employees at PT Pegadaian as gold appraisers who accept and assess gold collateral submitted by customers as debtors in the pawn credit process but it turns out that the collateral is the result of criminal acts that harm other parties so that the employee is considered a collector, as well as legal efforts that can be made by in terms of returning the collateral if it is decided by the Court to be returned to the victim who is considered the owner of the goods while the status of the collateral is a receivable that is still in process. In conducting research, the author uses data collection techniques and Court decisions, the results of this study state that employees who serve as gold appraisers cannot be drawn as a collector based on the provisions of Article 120 paragraphs 1, 2 and 3 of the P2SK Law. PT Pegadaian in returning losses resulting from court decisions in terms of returning the collateral to the victim, can take legal remedies through civil channels, but in practice sometimes it is not in accordance with what is regulated in the law.